Diversifying crops for food and trade - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Opinions from Dominica and St Kitts and Nevis about agricultural diversification, plus an FAO diversification project.